2024
DOI: 10.1111/rda.14541
|View full text |Cite
|
Sign up to set email alerts
|

Dystocia frequency and causes in horses with pregnancy disorders or a history of dystocia: A prospective study

Markus Ellerbrock,
Judith Krohn,
Kathrin Büttner
et al.

Abstract: Dystocia typically presents a life‐threatening condition for both the mare and the foal. This prospective long‐term study aimed to ascertain whether mares with prior pregnancy disorders or a history of dystocia were at a higher risk of experiencing subsequent dystocia in comparison to those without such medical antecedents. To achieve this goal, the authors analysed 207 parturitions and 164 mares over a 10‐year period. Of these, 57 were associated with pregnancy disorders or prior dystocia (Group 1), while 150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…This con rms the prevalent ndings of retrospective studies that equine dystocia is primarily of foetal origin [8, 13,14]. A recent prospective study on dystocia in horses also found that the causes of dystocia were more often foetal than maternal [15].…”
Section: Discussionsupporting
confidence: 79%
“…This con rms the prevalent ndings of retrospective studies that equine dystocia is primarily of foetal origin [8, 13,14]. A recent prospective study on dystocia in horses also found that the causes of dystocia were more often foetal than maternal [15].…”
Section: Discussionsupporting
confidence: 79%